Controlling the cost of risk management by utilising a phase portrait methodology - David Eaton; Seyyit Umit Dikmen; Rıfat Akbiyikli (Transport, 2018)
The methodology developed in this study presents an approach to the concurrent evaluation of Risk Management (RM) effectiveness during project execution. The method proposed is an adaptation of an approach developed and advocated by Khlebopros et al. (2007) for the mathematical modelling of complex systems, namely the analysis and effects of natural catastrophes. Hence, the method utilizes a phase portrait approach to identify the Prime Cost (PC) of RM of a project. Furthermore, the method provides an approach for comparing the individual identified risks with this PC, and subsequently highlighting a way of classifying and prioritising risks into a rank order for RM attention. The MERA (Multiple Estimating Risk Analysis) approach was utilized for the quantification of risk impact and ultimately the creation of the phase portrait. Besides being accurate and intuitively understandable, the methodology is relatively simple to implement and provides a rapid visualisation of the overall risk extent of a project.